2017
DOI: 10.1504/ijpm.2017.080916
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of costs in the Russian public procurement system

Abstract: Abstract:The growing attention of governments, international organisations and NGOs to public procurement issues over the last two decades has been accompanied by many studies on the efficiency of public procurement. However, few researchers have considered the costs of procurement regulation for public customers and private suppliers. This problem is especially acute for the public procurement system in Russia. In this paper we propose an approach to measuring public customers' procurement costs. We test this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
0
9
0
4
Order By: Relevance
“…We developed the methodologies for estimating public procurement costs at the regional level on the basis of the approach used in the PwC study (PwC, 2011). We also took into account the experience of piloting a cost estimation methodology for an individual public customer using a case study of the Voronezh State University (Balaeva and Yakovlev, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We developed the methodologies for estimating public procurement costs at the regional level on the basis of the approach used in the PwC study (PwC, 2011). We also took into account the experience of piloting a cost estimation methodology for an individual public customer using a case study of the Voronezh State University (Balaeva and Yakovlev, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The authors tested the proposed model for measuring the additional costs of purchasing using data from a large construction JOPP 18,1 firm in Italy. Balaeva and Yakovlev (2017) used a case study of one organization to evaluate the costs of a public customer throughout the full procurement cycle. The authors showed that the customer's costs vary strongly depending on the type of procedure.…”
Section: Estimation Of Procurement Costsmentioning
confidence: 99%
See 3 more Smart Citations